Ozone oxidized lignin-based polyurethane with improved properties. (August 2019) - Zhang, Yumei; Yan, Ru; Ngo, Tri-dung; Zhao, Qi; Duan, Jinchi; Du, Xinwei; Wang, Yuliang; Liu, Baijun; Sun, Zhaoyan; Hu, Wei; Xie, Haiming
Graphical abstract: Lignin was oxidized by ozone, and the oxidized lignin was used to synthesize lignin based polyurethane which presented an improved tensile strength. Highlights: The –OH content of lignin was much increased through the ozone oxidation. The oxidized lignin was used to react with HDI to produce LBPU. The obtained LBPU presented excellent mechanical and coating properties. Abstract: Lignin is the second most abundant source of renewable raw materials. In this study, a novel oxidation method for lignin by ozone was reported to obtain oxidized lignin (OL). The hydroxyl content of lignin was increased, and the content of phenolic hydroxyl was increased from 0.715 to 1.015 mmol/g when the ozone oxidized time was 0.5 h. Then the OL was used to substitute part of PEG200 and react with isocyanate to produce lignin-based PU pre-polymer. After curing, oxidized lignin based PU (OLPU) was obtained. Owing to the rigid aromatic structure of lignin and crosslinking, the OLPU presented excellent properties. The 0.5-OL20 PU (lignin was oxidized 0.5 h by ozone with the rate of 3.2 g/h, and the lignin content was 20% in OLPU) presented the tensile strength of up to 47.2 MPa, and its gel content reached 97.9%. The OLPU film also presented high hydrophobicity and thermal stability. The hardness of OLPU coatings could be 2H. Thus, the lignin oxidized by ozone can be applied in the lignin based PU, and the oxidized lignin based PU is promising for the wider application.